Development of a solenoid actuated planar valveless micropump with single and multiple inlet–outlet arrangements. (16th June 2016) - Kumar, N; George, D; Sajeesh, P; Manivannan, P V; Sen, A K
Abstract: We report a planar solenoid actuated valveless micropump with multiple inlet–outlet configurations. The self-priming characteristics of the multiple inlet–multiple outlet micropump are studied. The filling dynamics of the micropump chamber during start-up and the effects of fluid viscosity, voltage and frequency on the dynamics are investigated. Numerical simulations for multiple inlet–multiple outlet micropumps are carried out using fluid structure algorithm. With DI water and at 5.0 Vp-p, 20 Hz frequency, the two inlet–two outlet micropump provides a maximum flow rate of 336 μ l min −1 and maximum back pressure of 441 Pa. Performance characteristics of the two inlet–two outlet micropump are studied for aqueous fluids of different viscosity. Transport of biological cell lines and diluted blood samples are demonstrated; the flow rate-frequency characteristics are studied. Viability of cells during pumping with multiple inlet multiple outlet configuration is also studied in this work, which shows 100% of cells are viable. Application of the proposed micropump for simultaneous pumping, mixing and distribution of fluids is demonstrated. The proposed integrated, standalone and portable micropump is suitable for drug delivery, lab-on-chip and micro-total-analysis applications.